Antibody Response in Seropositive Multiple Sclerosis Patients Vaccinated with Attenuated Live Varicella Zoster Virus - RT Ross; MR Dawood; Mary Cheang; Lindsay E Nicolle (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the safety and effectiveness of live attenuated varicella zoster virus (VZV) vaccine (OKA/Merck) on 50 patients with chronic progressive multiple sclerosis (MS), based on the hypothesis that VZV might be the antigen or antigen mimic of MS plus the fact that repeated high antigen doses have produced ‘antigen paralysis’ in experimental allergic encephalomyelitis mice.